2014
DOI: 10.12691/ajcea-2-3-4
|View full text |Cite
|
Sign up to set email alerts
|

Development and Impact of the Egyptian Climatic Conditions on Flexible Pavement Performance

Abstract: Pavements are subject to environmental conditions, which affect the performance of both flexible and rigid pavements. The current flexible pavement design system in Egypt relies primarily on the 1993 American Association of State Highway and Transportation Officials (AASHTO) Design Guide. The method has many limitations. One of the serious limitations is the empirical drainage layer coefficients. These coefficients in addition to the seasonal variation of the roadbed resilient modulus are the only environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 7 publications
(8 reference statements)
0
20
0
1
Order By: Relevance
“…They concluded that variabilities in precipitation and, thus, in soil moisture, can reduce road design reliability, although the climate change signal may be minimal in terms of precipitation. Similar studies were also conducted for the USA, Canada, and Egypt [68][69][70][71][72][73].…”
Section: Quantitative Assessment Methodsmentioning
confidence: 53%
“…They concluded that variabilities in precipitation and, thus, in soil moisture, can reduce road design reliability, although the climate change signal may be minimal in terms of precipitation. Similar studies were also conducted for the USA, Canada, and Egypt [68][69][70][71][72][73].…”
Section: Quantitative Assessment Methodsmentioning
confidence: 53%
“…1. The climatic data for these locations were generated as part of another study by the authors of this paper [12,13]. The weather properties of the three locations are shown in Table 4.…”
Section: Mepdg Simulation Runsmentioning
confidence: 99%
“…Various aspects of the impact of environmental polystructures on a linear structure are considered with respect to the stage of its life cycle. For the purpose of control of road structures with the account of environmental factors impact, regulatory documents and design guidelines adopted in different countries provide the use of systematized territorial zoning data [1][2][3][4][5]. Today, development of reliable road structures requires building regional climatic models and using special software to include the optimization techniques in the design process [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Various approaches exist for solving road climatic zoning issues, they are based on assessment of various conditions, including environmental and climatic, geological and geographical, physico-climatic parameters of the territory [5,9]. Differentiation methods (division of territories) used for transport infrastructure design are developed on the basis of the general theory of physico-geographic zoning with the account of the industry peculiarities.…”
Section: Introductionmentioning
confidence: 99%